2003
DOI: 10.1080/02791072.2003.10399988
|View full text |Cite
|
Sign up to set email alerts
|

The Historical Trauma Response Among Natives and Its Relationship with Substance Abuse: A Lakota Illustration

Abstract: Historical trauma (HT) is cumulative emotional and psychological wounding over the lifespan and across generations, emanating from massive group trauma experiences; the historical trauma response (HTR) is the constellation of features in reaction to this trauma. The HTR often includes depression, self-destructive behavior, suicidal thoughts and gestures, anxiety, low self-esteem, anger, and difficulty recognizing and expressing emotions. It may include substance abuse, often an attempt to avoid painful feeling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
219
0
6

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 613 publications
(227 citation statements)
references
References 7 publications
2
219
0
6
Order By: Relevance
“…They agree with other scholars that trauma destroys a person's faith, decency, courage, and connection. The power of group sharing or sharing circles resulted in a reawakening of the feeling of connection with others through relationships that were the result of altruism by others in the group (Brave Heart, 2003;Drake, 2003;Duran, 2006;Herman, 2006;Marsh, 2010;Yalom & Leszez, 2005). Yalom and Leszez (2005) also stated that individuals in groups mirror the actions of others and, in so doing, the survivor recognizes and claims a lost part of himself or herself.…”
Section: The Medicine Wheel and The First Quadrantmentioning
confidence: 99%
“…They agree with other scholars that trauma destroys a person's faith, decency, courage, and connection. The power of group sharing or sharing circles resulted in a reawakening of the feeling of connection with others through relationships that were the result of altruism by others in the group (Brave Heart, 2003;Drake, 2003;Duran, 2006;Herman, 2006;Marsh, 2010;Yalom & Leszez, 2005). Yalom and Leszez (2005) also stated that individuals in groups mirror the actions of others and, in so doing, the survivor recognizes and claims a lost part of himself or herself.…”
Section: The Medicine Wheel and The First Quadrantmentioning
confidence: 99%
“…129 Human studies have shown significant relationships between drug use and secondary social status, particularly exposure to current and historical racial discrimination. 130 Difficulty in successfully regulating emotional responses to social stressors, such as racial discrimination, is also associated with higher levels of drug use in humans. 131 Chronic stressors such as racial discrimination may also increase susceptibility to viral infections (such as HIV infection).…”
Section: Racial Discrimination: a Risk Factor For Child Health Disparmentioning
confidence: 99%
“…As a result of colonialism, cultural loss, historical trauma, and ongoing exposure to traumatic experiences, AIs contend with substance abuse issues at higher rates than members of other racial and ethnic groups (Brave Heart, 2003;Morgan & Freeman, 2009;Walter et al, 2002). The mounting impact of intergenerational stress and trauma, such as the forced removal of AI children and current-day fear of the child welfare system (Myhra & Wieling, in press), stunts the progress of cultural and emotional growth and ultimately creates vulnerabilities to substance abuse and related maladaptive coping behaviors (Brave Heart, 1999;Duran & Duran, 1995;Gray, 1998).…”
Section: Sociohistorical Contextmentioning
confidence: 95%
“…The mounting impact of intergenerational stress and trauma, such as the forced removal of AI children and current-day fear of the child welfare system (Myhra & Wieling, in press), stunts the progress of cultural and emotional growth and ultimately creates vulnerabilities to substance abuse and related maladaptive coping behaviors (Brave Heart, 1999;Duran & Duran, 1995;Gray, 1998). Spirituality, religion, and practicing cultural traditions, along with connection to family and tribal communities, have been identified as key factors associated with healing from cultural trauma for many AI families and communities (Brave Heart, 2003;Jervis & AI-SUPERPFP team, 2009;Walters, 1999).…”
Section: Sociohistorical Contextmentioning
confidence: 98%
See 1 more Smart Citation